C-reactive protein : determinant value predicting length of stay in dengue patient attending emergency department HUSM Kubang Kerian - Md Supian, Badrul Hisham (2015)

(untitled)
Title: C -reactive Protein: Determinant value predicting length of stay in dengue patient attending Emergency Department HUSM Kubang Kerian, Kelantan. Background: C-reactive protein is simple and cheap laboratory parameters that can be use in Emergency Department or inpatient ward to predict hospital stay and severity of disease. Objectives: To determine association between C-reactive protein between length of stay, severity of disease and survival rate of dengue patient in Emergency Department. Methodology: A cross-sectional study of adult confirmed dengue patients (age between 18-70 years) presented to ED Hospital Universiti Sains Malaysia then subsequently admitted to the medical ward. Length of stay, severity and survival rate of dengue patient was assessed in relation to C-reactive protein level. Results: Fifty patients were included during study period of 6 months. From this study, it showed that there was significant increase level of C-reactive protein with longer hospital stay and in severe dengue patient. For this study, mean length of stay was 4 days for patient with high level of c-reactive protein. However, from Mann Whitney U test, it was shown that there was no significant correlation between CRP level and length of stay with p-value of 0.28. There was also, higher level of C-reactive protein in patient who developed severe dengue. But from Chi-square test, was no significant correlation between CRP level with risk of develop into severe dengue. Conclusion: In conclusion, despite of few limitations in our study has shown no correlation between CRP level and length of stay, severity of clinical course or mortality in dengue patient .